The Effect of Occupational Health and Safety (OHS) Knowledge and Organizational Commitment on Employees’ Ability to Minimize Workplace Accidents at Hospital X, Surabaya - Dwi Nisa Widhawati; Kun Setiyono; Retno Susanti (Asosiasi Dosen Muda Indonesia, 2026)
Workplace accidents remain a critical Occupational Health and Safety (K3/OSH) issue, particularly in hospitals where employees are exposed to multiple hazards and high work intensity. Strengthening employees’ ability to minimize workplace accidents is essential to protect staff, maintain service continuity, and improve organizational performance. In this context, K3/OSH knowledge and organizational commitment are assumed to be key factors supporting accident-prevention capability. Objective: This study aims to analyze the effects of K3/OSH knowledge and organizational commitment on employees’ ability to minimize workplace accidents at Hospital X Surabaya, both simultaneously and partially. Methods: This study employed a quantitative, cross-sectional design. Data were collected using a structured questionnaire administered to 84 employees selected from a population of 179 using Slovin’s formula (e = 0.10). Respondents included clinical and non-clinical staff (doctors, nurses, midwives, medical record officers, pharmacists, radiology staff, and administrative personnel). Data were analyzed using multiple linear regression with SPSS, assessing the overall model significance (F-test) and the partial effects of each predictor (t-tests). Results: The regression model was statistically significant, indicating that K3/OSH knowledge and commitment jointly predict accident-minimization ability (F = 142.686, p < .001). Partially, K3/OSH knowledge had a significant positive effect on accident-minimization ability (t = 4.423, p < .001), and organizational commitment also had a significant positive effect (t = 3.104, p = .003). These results suggest that employees’ ability to minimize workplace accidents tends to increase when they have stronger OSH knowledge and higher commitment. Implications: Hospitals should implement integrated OSH interventions that combine competency development (e.g., role-specific K3 training, SOP reinforcement) with commitment strengthening (e.g., leadership consistency, safety culture reinforcement, supportive supervision) to enhance accident prevention. Originality: This study provides context-specific evidence from an Indonesian hospital by testing K3/OSH knowledge and commitment simultaneously within one predictive model across diverse occupational roles, highlighting the need for combined knowledge–commitment strategies in accident prevention.